Learning obstacles on fractions: A scoping review - Sari, Indah Puspita; Suryadi, Didi; Herman, Tatang; Dahlan, Jarnawi Afgani; Supriyadi, Edi (IKIP Siliwangi and I-MES, 2024)
This scoping review aims to consolidate the research that has been conducted on fractional learning challenges, with a particular emphasis on the various student groups, intervention strategies, outcomes, and specific learning problems. The research finds essential research topics and relevant papers and extracts data in order to gain an understanding of the intricate nature of fraction learning. The technique utilized in this study is a five-stage process. The preliminary literature searches produced a total of twenty-three articles, seven of which were chosen for a more in-depth examination. These publications covered a variety of themes, including the effectiveness of manipulatives, strategies for accommodating students who struggle with mathematics, focused training interventions, and instructor guidance. The findings of this research shed light on the myriad of difficulties associated with learning fractions. These difficulties range from basic conceptual and procedural comprehension to unique educational obstacles for a wide variety of student populations, including those with learning disabilities. The study focuses on a variety of intervention tactics, such as accommodations, strategic training, and the utilization of manipulatives, with the objective of enhancing problem-solving abilities, conceptual comprehension, and procedural proficiency in fractions. This all-encompassing examination highlights the ubiquity of misconceptions and the necessity of explicit training. It also highlights the usefulness of direct instruction, strategic education, and problem-solving exercises in improving students' comprehension of fractions. In order to overcome problems in learning fractions and to improve mathematical education, the findings advocate for the continuation of research and the incorporation of effective pedagogical approaches.